A escola e a divulgação científica : um estudo na cidade de Toledo - PR - Bertoldo, Raquel Roberta (2015)
This work contemplates the results of researches conducted in the years 2013 and 2014. We intend to verify if the high schools, located in the city of Toledo / PR, Brazil, perform scientific disclosure activities and how students recognize it and accept these kind of activities. As a theoretical support, we used the concepts of scientific culture, scientific enculturation and scientific disclosure. The survey was conducted in two stages. The first one was consisted on mapping all schools of the city of Toledo, in which we found through interviews with some professionals and students if they performed scientific disclosure activities and what were those activities. From the initial mapping, we selected two schools for the second stage. The criterion for selection was: larger amount of scientific disclosure activities, frequency of activities and involvement of a greater number of students. Thus, in the second stage of the research, we interviewed students from 2nd and 3rd year of high school of these two schools, using the focal group methodology. It was discussed in the group how the activities related to science in school are carried out and how is the participation of students. The analysis of data followed the content analysis proposed by Bardin (1977) .The results of the first stage showed that most of the schools perform little or does not perform scientific disclosure activities and that most of the respondents do not see science as culture. They also do not understand the scientific disclosure as a discursive genre that should be worked on classes. The data of the second stage showed that students are interested in scientific disclosure activities performed at school, considering that the science fairs were widely commented. The group of PIBID - Chemical, which operates in both schools was mentioned by students, who said the project at the University conducts various interesting activities beyond assisting at other moments (science fairs, tutoring, experimental classes).Some activities promoted by school, mainly on reading, has no good acceptation by the students, requiring a new schedule. Thus, the process of formation of scientific culture and, consequently, the scientific enculturation of the students, do not have the school as a formative element, considering that it has contributed a little to this process. We hope with this research, (re) think the school's role in scientific enculturation process